Investigate the concept of Festival and Celebration among Cultural and Historical Building - Dadman, Enayatullah; Madani , Saied Mohsen Saiedi (The Indonesian Journal of Social Studies, 2022)
Festivals and celebrations are both occasions and events that are marked by people's delight, mirth, and enjoyment. Both events are usually performed in front of audience. The goal of this study was to determine the correct meaning of the two words Festival and Celebration in relation to cultural and historical structures. As a result, utilizing the library technique, we attempted to obtain reliable information from actual books.The findings show that In some manner, all celebrations are cultural. All festivals and Celebrations convey the same message of love, perseverance, and understanding. At these gatherings, we express our gratitude to God for the unusual event or occasion that began on this particular day. There is no written history to show when festivities began, although they were celebrated in ancient Greece and Rome for religious, social, and political reasons. Celebrations have a huge impact on feelings of social togetherness. Many of these events focus on social or ethnic issues, and they aim to inform community members about their customs.